Access to archival collections about brazilian federal universities’ monuments through “Access to Memory” platform - Billig Schäfer, Murilo; Leite da Silva, Eva Cristina (Advanced Notes in Information Science, 2023)
This study proposes utilizing the records description and diffusion platform “Access to Memory” to promote access to archival collections kept in the permanent archives of Brazilian federal universities related to monuments within such institutions. The initiative is in the Digital Humanities area, which advocates the adoption of digital tools aimed at promoting and developing actions and studies that result in knowledge production for the Humanities. This study shows that Information Science, Archival Science, and Digital Humanities can establish convergent actions that are fundamental in a society more and more adhesive to digital resources. We can conclude that adopting the digital tool “Access to Memory” to provide access to archives and information referring to monuments of federal universities stimulates reflection and comprehension about these symbolic objects that represent the culture, the memory, and the history of the country.